A review of solar photovoltaic-thermoelectric hybrid system for electricity generation. (1st September 2018) - Li, Guiqiang; Shittu, Samson; Diallo, Thierno M.O.; Yu, Min; Zhao, Xudong; Ji, Jie
Abstract: Solar energy application in a wider spectrum has the potential for high efficiency energy conversion. However, solar cells can only absorb photon energy of the solar spectrum near the solar cell band-gap energy, and the remaining energy will be converted into thermal energy. The thermoelectric generator is a good choice to utilize this thermal energy. This paper analyses the feasibility of photovoltaic-thermoelectric (PV-TE), and reviews the current types and performance of PV-TE. Furthermore, it presents the optimization and development of PV-TE. In addition, this paper presents the challenge and efficient improvement of PV-TE in actual application. Therefore, this paper would provide a valuable reference for further research into the field of PV-TE and its applications. Highlights: The performance and recent advances in PV-TE are presented. The challenge faced in the field of PV-TE and solutions are indicated. Current state of art in PV-TE for electricity generation is presented. Optimization and development of PV-TE is demonstrated.